Exam Scheduling Preferences and Their Impact on Student Well-Being and Performance: A Call for Objective Evaluation and Supportive Interventions [Letter] - El-Jabri T; Rahman O; Khan AHA (Advances in Medical Education and Practice)
Talal El-Jabri, Obaid Rahman, Ameer Hamid A Khan Addenbrooke’s Hospital, Cambridge University Hospitals NHS Trust, Cambridge, UKCorrespondence: Talal El-Jabri, Cambridge University Hospitals NHS Trust, Cambridge, UK, Email talal.el-jabri1@nhs.net